Minor edible fruits of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2019)
Minor edible fruits are the genetic resource of a country, playing a vital role as food, nutrition and medicine. Bangladesh having both tropical and sub-tropical climatic condition possesses a large number of species that produce minor edible fruits. The present study represents 255 species of minor edible fruit yielding plants of Bangladesh. Of them, 242 species belong to 58 families of Magnoliopsida and 13 species to three families of Liliopsida. The large minor fruit yielding families are Euphorbiaceae (20 spp.), Myrtaceae (18 spp.), Moraceae (15 spp.), Arecaceae (11 spp.), Sapindaceae (11 spp.), Anacardiaceae (10 spp.), Annonacae (10 spp.), Rutaceae (8 spp.), Verbenaceae (8 spp.) and Vitaceae (8 spp.). Three species are aquatic in nature and about 50 species are herbs, including 31 species of climbers or lianas, and 49 are shrubs and the remaining 156 species are trees. About 48 species are cultivated for fruits and the 35 species are both cultivated and wild. The remaining species are exclusively wild. A totalof 53 exotic species are included in the cultivation. In most of the species, pericarp with mesocarp or the whole part of fruit is edible. In few cases either seed or kernel is edible, or in others the non-carpel part of flower. Summer is found as the most and winter as the least suitable fruit yielding seasons in a year.